Rabiṭhākurera mā - Mukhopādhyāẏa, Praṇabakānti (Nātha Pābaliśiṃ, 2010)
On the life of Sarada Devi, 1830-1941, mother of Rabindranath Tagore, a Bengali litterateur
Includes bibliographical references. - In Bengali-Schr
Keywords: Sarada Devi 1830-1875; Tagore; Rabindranath 1861-1941; Mothers of authors